Chidamide-based 3-drug combination regimen reverses molecular relapse post transplantation in AML1-ETO–positive acute myeloid leukemia - Xi, Yang; Chenglong, Li; Rong, Zhang; Wen, Wang; Yu, Wang; Jiao, Chen; Juan, Huang; Feifei, Che; Rong, Xiao; Tao, Jiang; Hui, Li; Xiaobing, Huang (Frontiers in Pharmacology, 2023)
Objective: We aimed to explore a new method to reverse early relapse in patients with AML1-ETO–positive acute myeloid cell transplantation. Methods: A chidamide-based 3-drug combination regimen was used in our center to treat patients with AML1-ETO–positive AML post transplantation but negative flow cytometry results. A retrospective analysis was performed of the survival rate and possible influencing factors of patients with relapse treated with this regimen in our center from January 2018 to January 2022. Results: The overall response rate was 95.8% (23/24), and the median number of treatment courses was 4 (range, 3–12 courses). The total molecular complete response (MCR) was 79.1% (19/24) after all treatments, and the molecular complete response was 37.5% (9/24) after one cycle of treatment but reached 58.3% (14/24) after four cycles; overall, the proportion of MCR increased gradually with the increase in treatment cycles. The projected 5-year overall survival rate was 73.9%. The projected 5-year leukemia-free survival rate was 64.8%, and the projected 1-year cumulative relapse rate was 35.5%. The incidence of grade II–IV graft-versus-host diseases (GVHD) was 29.2% (7/24), and that of grade III–IV GVHD was 20.8% (5/24), which could be effectively controlled by glucocorticoid therapy combined with calcineurin inhibitors The total incidence of chronic GVHD was 29.2% (7/24), and all cases were localized chronic GVHD. The total infection rate was 33.3% (8/24), mainly involving bacterial and fungal infections, and the incidence of life-threatening infections was 4.17% (1/24). The treatment-related mortality rate was 0%; and the total mortality rate was 20.8% (5/24). Nausea and vomiting, thrombocytopenia, and neutropenia were common adverse reactions, all of which were Common Terminology Criteria for Adverse Events grade 2–3 events and reversible after drug withdrawal. In terms of immunity, Th1 cell counts gradually increased, Th17 cell counts gradually decreased, and the Th1/Th17 ratio gradually increased after treatment. The CD8+ T lymphocyte count increased gradually, while the CD4+ T lymphocyte count did not change significantly. Conclusion: Our chidamide-based 3-drug combination regimen led to a high remission rate and tolerable adverse reactions in patients with AML1-ETO–positive post-transplant relapse, and most patients can achieve long-term survival with this regimen.